Loss of Giant Kelp, Macrocystis pyrifera, Driven by Marine Heatwaves and Exacerbated by Poor Water Clarity in New Zealand - Tait, Leigh W.; Thoral, François; Pinkerton, Matthew H.; Thomsen, Mads S.; Schiel, David R. (Frontiers in Marine Science, 2021)
Marine heatwaves (MHW) are becoming stronger and more frequent across the globe. MHWs affect the thermal physiology of all biological organisms, but wider ecosystem effects are particularly impactful when large habitat-forming foundation species such as kelps are affected. Many studies on impacts from MHWs on kelps have focused on temperature effects in isolation, except for a few studies that have integrated co-occurring stress from grazers, wave exposure and nutrient limitation. It is likely that many stressors act in concert with MHWs and exacerbate their effects. Here we analyzed satellite images over 60 months to assess temporal changes in abundance of surface canopies of the giant kelp Macrocystis pyrifera in the New Zealand coastal zone. The analysis encompassed the most extreme MHW on record (2017/18), across a 6° latitudinal gradient of four regions southward from the northern distributional limit of Macrocystis along mainland New Zealand. We tested the association of surface canopy cover of Macrocystis with sea surface temperature, temperature anomalies, chlorophyll-a (a proxy for nutrient availability) and water clarity (diffuse attenuation coefficient). We found a reduced cover of Macrocystis across all regions during and after the 2017/18 MHW, with least impact at the most southern region where the maximum temperatures did not exceed 18 ˚C. There was also an important and significant interaction between temperature and water clarity, showing that temperature-induced kelp loss was greater when water clarity was poor. These results show that notable negative effects occurred across the coastal range of this foundation species and highlight the importance of studying MHW effects across latitudinal gradients and in concert with other co-occurring stressors.